The concept of Halal and Halal food certification process in Malaysia: issues and concerns - Asa, Rokhsana Shirin; Abdul Ghani Azmi, Ida Madieha (The Malaysian Consumer and Family Economics Association, 2017)
The process of halal certification is dependent on the construction of what is deemed to be falling with the halal parameters set by the Quran and Sunnah, being the two primary sources of the Shari'ah, and supplemented with juristic opinion and issuance of fatwa by national religious authorities. In Malaysia, the authority responsible for halal certification is JAKIM while the authority responsible to provide rulings on halalness is the National Fatwa Committee. This article examines the guiding principles for he conceot of halal in the Quran and Sunnah and the collection of fatwa on food products by the National Fatwa Committee. Together, the three sources constitute the yardstick to the implementation of halal in Malaysia. Using content analysis, the article analyses the meaning and construct of the three primary sources and examine issues and concerns arising from the implementation of halal certification process in Malaysia. the article also highlights the views of Yusuf al Qaradhawi, being the most prominent scholar on the underlying principles of what constitute halal and haram. The article concludes that whilst the Quran has outlines the general principles for the determination of halalness, there is a considerable degree need for guidance from the religious bodies in the form of fatwa on any recurrent issues pertaining to food products and processes.